Ava's poppy - Pfister, Marcus (NorthSouth, 2012)
Ava is delighted when she discovers a red poppy in the field of her house. She sits with the flower in the sunny days of summer and shields it in the rain until one day the petals start to drop and the beautiful flower fades. But when spring comes again, Ava is surpised anew.